Sleeve gastrectomy and Roux-en-Y gastric bypass lead to comparable changes in body composition after adjustment for initial body mass index - Otto, Mirko; Krammer, Johannes; Weiß, Christel; Kienle, Peter (Obesity surgery, 2016)
Background: Bariatric surgery is a safe and established treatment option of morbid obesity. Mere percentage of excess weight loss (%EWL) should not be the only goal of treatment. Methods: One hundred seventy-three obese patients were included in the study. They underwent either Roux-en-Y gastric bypass (RYGB; n = 127, mean body mass index (BMI) 45.7 ± 5.7 kg/m2) or sleeve gastrectomy (SG; n = 46, mean BMI 55.9 ± 7.8 kg/m2) for weight reduction. Body weight and body composition were assessed periodically by bioelectrical impedance analysis. Results: After 1 year of observation, %EWL was 62.9 ± 18.0 % in RYGB and 52.3 ± 15.0 % in SG (p = 0.0024). Body fat was reduced in both procedures with a slight preference for SG, and lean body mass was better preserved in the RYGB group. Due to significant differences in the initial BMI between the two groups, an analysis of covariance was performed, which demonstrated no significant differences in the %EWL as well as in the other parameters of body composition 1 year after surgery. Using percentage of total weight loss to evaluate the outcomes between the two procedures, no significant difference was found (31.7 ± 8.4 % in RYGB and 30.5 ± 7.6 % in SG patients, p > 0.4). Conclusions: Excess weight loss is highly influenced by the initial BMI. Total weight loss seems to be a better measurement tool abolishing initial weight differences. SG and RYGB do not differ in terms of body composition and weight loss 1 year after surgery.